Single molecule analysis reveals monomeric XPA bends DNA and undergoes episodic linear diffusion during damage search - Emily C. Beckwitt (Nature Portfolio, 2020)
It is not fully understood how XPA interacts with a DNA lesion during nucleotide excision repair. Here, the authors use single molecule analysis to study XPA–DNA interactions, including the DNA bend angle, protein stoichiometry, and diffusive properties during damage search.